PENGARUH KREDIBILITAS ORANG TUA TERHADAP PERILAKU KONSUMSI MEDIA DIGITAL GENERASI ALPHA - Jannah, Maisal; Hatta, Kusmawati; Balqis, Awanda (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
The study aims to explore the influence of parents' credibility on the digital media consumption behavior of Alpha Generation children from a psychological point of view. By adopting psychological theories such as attachment theory and social learning theory, the study identified the relationship between parents' credibility and their children's patterns of digital media consumption. The Alpha generation, the generation born after 2010, grew up in a digital age full of social media and advanced technology. The research method used was a survey method, by distributing questionnaires to Alpha Generation parents to find out their perceptions of their credibility in influencing their children's digital media consumption behavior. Children who think their parents have credibility. The majority of Alpha Generation kids are very active on social media, with most of them using this platform every day. Confidence in parents as sources of information about digital media varies, with about half of respondents believing in their parents, while others are not or feel unsure. It shows an opportunity for parents to increase their credibility in providing information about digital media. Decisions to trust information from parents or peers depend heavily on the topic discussed, which suggests that children tend to look for relevant and credible information depending on the context.